(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
Spray drying is a conventional technique for converting liquids into powders, involving preparation, homogenization, atomization, dispersion, and drying. However, electrostatic charges on the drying chamber walls and powder particles often cause adhesion and buildup, reducing process efficiency and cleanliness. This study aims to identify the types of electrical charges on powder particles contributing to impurity formation and to reduce such deposits by introducing alternating repulsive charges based on the dominant charge polarity. A total of 1,200 ml of full cream milk was subjected to spray drying, and the powder charge profile was measured using a multimeter to determine polarity in three replications. A system modeled after a Dual Output DC Power Supply applied repulsive charges through aluminum foil on the inner surface of a borosilicate chamber, generating 1140 Coulomb (C) of repulsive charge for each replication (Profiles 1–3, n = 3). The resulting electric charges were 5.0×10⁻⁵ ± 1.73 C, 4.0×10⁻⁵ ± 1.73 C, and 4.0×10⁻⁵ ± 1.73 C of positive polarity (p>0.05). Comparisons of powder weight collected with and without repulsive charge application were 0.204 ± 0.082 g and 0.254 ± 0.080 g, respectively. Although powder weight decreased with repulsive charge, the difference was not statistically significant (p>0.05). These findings indicate that alternating repulsive charges have limited effectiveness in minimizing impurity deposits or enhancing spray drying efficiency, likely due to complex interactions involving charge behavior, temperature, and humidity. Future work should explore detailed models incorporating particle size, shape, and electroconductivity to better understand fouling mechanisms.